How does emotional intelligence buffer the relationship between social media addiction and symptoms of eating disorders? Cross validation of two moderated mediation models. - Peláez-Fernández, María Ángeles; Extremera-Pacheco, Natalio; Mills, Jennifer S. (My University, 2024)
Although it is well documented the influence of social media addiction on both thin ideal internalization and body dissatisfaction with the subsequent consequences on eating disorders (ED) symptomatology, no prior studies have yet tested the potential moderator role of emotional intelligence (EI) in the links between thin ideal internalization and ED symptoms, and body dissatisfaction and ED symptoms. To bridge these gaps, this study tested two moderated mediation models explaining ED symptomatology. We hypothesised that EI buffers the effect of social media addiction on ED symptoms through thin ideal internalization and body dissatisfaction. A sample composed of 407 Spanish graduate students and community adults completed measures of EI, social media addiction, thin ideal internalization, body appreciation scale, and ED symptomatology. EI moderated the relationship between thin ideal internalization and ED symptoms and between body dissatisfaction and ED symptoms. The findings suggest that EI has specific buffering effects of the influence of social media addiction on thin ideal internalization and body dissatisfaction reducing ED symptomatology. We discuss the implications of these findings for efforts to deal with the detrimental effects of social media addiction on ED symptomatology.
Keywords: Madurez afectiva; Redes sociales en Internet; Adicción; Conducta alimentaria - Trastornos; Emotional intelligence; Social media addiction; Eating disorders